Compressive Behavior of Interlocking Plastic Blocks Structural Elements Having Slenderness - Adnan, Muhammad; Khalid, Faiza; Ali, Majid (Buildings (Basel), 2022)
Earthquakes are among of the most harmful and potentially fatal natural disasters. Masonry structures in seismic zones of urban and rural areas around the world pose a threat to human life. Housing that is both affordable and earthquake-resistant in earthquake-prone areas is currently in demand in developing countries. For affordable earthquake-resistant structures in earthquake-prone areas, numerous researchers have studied mortar-free interlocking structures. Plastic blocks are used in order to reduce the mass of the overall structure. To start with, structures under gravity are explored first because more than 95% of its design life, any structure has to withstand gravity. Prototypes of interlocking plastic-block columns, solid walls, and walls with an opening are considered for making the mortar-free structures. In this study, the effect of slenderness on the behavior of interlocking-plastic-block structural elements is investigated under compressive loading by a servo-hydraulic testing machine in the laboratory. The effect of slenderness on the behavior of one and two-block-wide structural elements was investigated in terms of the stress–strain curve, energy absorption, and toughness index under compressive loadings. Correlations between the compressive strength of interlocking-plastic-block structural elements with varying thicknesses were found. Scaled-down prototypes of interlocking-plastic-block structural elements having two-block wide depicted more resistance to compressive loads than one block wide structural elements. The correlations among the one and two block wide interlocking-plastic-block columns, single and double-block-wide solid walls, and single and double-block-width walls with an opening found in this analysis were Pdc = 2.2 Psc, Pdsw = 2.9 Pssw, and Pdwo = 3.5 Pswo. This study can be applied in the future to better understand the detailed behavior of interlocking plastic blocks.